A Location based security response mobile application: a case study of Nairobi CBD - Maturu, A. (Strathmore University, 2024)
Access to real-time reporting and response to security incidences has been a major issue in Kenya, with Nairobi, as the capital city, facing significant challenges. Over the years, the use of various forms of technology, including location-based services and emergency response systems, has been deployed to curb and report criminal activities in Kenya. Upon the occurrence of a crime, a victim usually reports it to the nearest police station, where they are issuedwith an OB (Occurrence Book) number for follow-up. At times, this system poses challenges, as response times to ongoing crimes are slow, and some victims shun off from reporting criminal activity due to poor response times or lethargic follow-up procedures. Moreover, the existing 999-call center, representing the current state of the art in emergency reporting, also demonstrates limitations in efficiency and response timeliness. This study aims to establish how location-based technology, specifically GPS (Global Positioning System), can be used to manage real-time reporting, response, and management of criminal activities within Nairobi. This research, therefore, proposed the development of a location-based mobile application that facilitates the easy reporting of crime to police stations and assignment of on-duty police officers to a criminal case. The application, developed using a hybrid approach to support both Android and iOS platforms, aims to facilitate real-time response to criminal activities, enhancing accountability, and transparency. The agile deployment methodology, particularly Scrum, will be used to ensure the inclusion of all stakeholders from the Product Owner to the Scrum Master and the End User throughout the development phase. This methodology also emphasizes iterations to ensure continuous improvement until the End- Release phase of the product. Data collection for the research is proposed to be achieved through purposive sampling of Kenyan citizens and residents who have been victims of crime, as well as through the utilization of the application by police officers handling criminal cases reported at police stations. Expected outcomes of implementing this application include improved response times to criminal activities, enhanced monitoring of cases by victims, and increased information accessibility for police officers, thereby significantly impacting security within Nairobi.
Full - text thesis